Crop Regulation in Pomegranate: I. Effect of Growth Regulators on Flower Induction, Sex Expression and Flower Drop - Ahire, G Z; Desai, U T; Choudhari, S M; Masalkar, S D (Annals of Arid Zone, 2016)
The studies carried out to regulate flowering in pomergranale. indicated that hand removal of flowers induces more flowers MH (1000 ppm). Carbaryl (7000 ppm). GA (20 ppm). NAA (250 10500 ppm) and Ethrel (250 10 500 ppm) produced less flowers than control. Ethrel al 500 ppm was the most effective in thinning Ihe Ilowers. GA induced more male Ilowers and less hermaphrodite flowers. Ethrel. MH and Carbary1 induced more hermaphrodile flowers.